A Key Based Hybrid Approach for Privacy and Integrity in Multi-Cloud - Abdul-Jabbar, Mariam Duraid; S.aldeen, Yousra abdul alsahib (Iraqi Journal of Science, 2023)
Before users store data in the cloud, many security issues must be addressed, as they will have no direct control over the data that has been outsourced to the cloud, particularly personal and sensitive data (health, finance, military, etc.). This article proposes a system based on chaotic maps for private key generation. A hybrid encryption for fast and secure cryptography. In addition to a multi-cloud storage with Pseudonymized file names to preserve user data privacy on the cloud while minimizing data loss. As well as a hash approach to check data integrity. AES in combination with RSA and fragmenting the file is used for the encryption. Integrity is cheeked using SHA-3. The experiments demonstrated that the key generation strategy may provide efficient keys in a shorter amount of time. Furthermore, the keys for the proposed approach passed NIST randomness testing. When cipher text fragmentation and encryption are combined, the average entropy value was (7.99). In addition, as file sizes grew, the total system's execution time increased only slightly.